Feeding brown algae and brown algae extracts from Saccharina Latissima to Broiler breeders - Kling, Stina (2021)
Brown algae and extracts of algae have been proved to have prebiotic effects. Seaweeds grow very fast and underwater. This is good from a sustainable point of view since algae do not need fertilizers, freshwater or agricultural land for growth. Brown algae is rich in nutrients, vitamins and minerals, and has an especially high content of iodine. This experiment included 45 hens and 9 roosters of the parent line of the fast-growing broiler ROSS 308. The hens were 28 weeks old at arrival and were housed in individual modules. There were three different experimental diets; algae meal (algae), algae extract and control. A boost vaccination was given 21 days after the introduction of the experimental diets. The aim was to analyse egg quality and transfer of antibodies and nutrients from hen to egg in order to determine if feeding broiler breeders brown algae and brown algae extracts could improve egg quality and transfer of antibodies and nutrients, and thereby, improve quality of newly hatched chicks. Maternal antibodies transferred from hen to chick during incubation are highly important since they protect the chick against pathogens during its first weeks in life. Healthy and vital chicks are the keys to good welfare and economic profit in poultry production.